Birth of a Be star: an APOGEE search for Be stars forming through binary mass transfer. Issue 3 (26th August 2022) - El-Badry, Kareem; Conroy, Charlie; Quataert, Eliot; Rix, Hans-Walter; Labadie-Bartz, Jonathan; Jayasinghe, Tharindu; Thompson, Todd; Cargile, Phillip; Stassun, Keivan G; Ilyin, Ilya
ABSTRACT: Motivated by recent suggestions that many Be stars form through binary mass transfer, we searched the APOGEE survey for Be stars with bloated, stripped companions. From a well-defined parent sample of 297 Be stars, we identified one mass-transfer binary, HD 15124. The object consists of a main-sequence Be star ($M_{\rm Be}=5.3± 0.6\, {\rm M}_{\odot }$ ) with a low-mass ($M_{\rm donor}=0.92± 0.22\, {\rm M}_{\odot }$ ), subgiant companion on a 5.47-d orbit. The emission lines originate in an accretion disc caused by ongoing mass transfer, not from a decretion disc as in classical Be stars. Both stars have surface abundances bearing imprint of CNO processing in the donor's core: the surface helium fraction is Y He ≈ 0.6, and the nitrogen-to-carbon ratio is 1000 times the solar value. The system's properties are well-matched by binary evolution models in which mass transfer begins while a $3-5\, {\rm M}_{\odot }$ donor leaves the main sequence, with the originally less massive component becoming the Be star. These models predict that the system will soon become a detached Be + stripped star binary like HR 6819 and LB-1, with the stripped donor eventually contracting to become a core helium-burning sdO/B star. Discovery of one object in this short-lived (∼1 Myr) evolutionary phase implies the existence of many more that have already passed through it and are now Be + sdO/B binaries. We infer that $(10-60)\, {{\ \rm per\ cent}}$ of Be stars have stripped companions, most of which are $\sim 100\, ×$ fainter than the Be stars in the optical. Together with the dearth of main-sequence companions to Be stars and recent discovery of numerous Be + sdO/B binaries in the UV, our results imply that binarity plays an important role in the formation of Be stars.